(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
Sweet potato is an important food crop in Eastern Ethiopia, including the West Hararghe Zone. However, the area is still far behind in attaining the required optimum productivity of Sweet potato, this is due to biotic and abiotic factors, inappropriate Agronomic practices and lack of improved variety, to tackle these problems; variety improvement research is the major one. Therefore, the objectives of the study were to estimate the magnitudes of genotype, environment, and genotype by environment interaction effects on Sweet potato genotypes and to identify the high yielder and stable genotypes for wide adaptability in West Hararghe Zone, Eastern Ethiopia. The experiment was carried out at two locations (Mechara on station and Habro district) in three consecutive years (2018–2020) on 20 Sweet potato genotypes using a randomized complete block design (RCBD) with three replications. Additive main effects and multiplicative interactions analysis (AMMI) indicated that the yield performances of genotypes were under the major environmental effects of genotype by environmental interactions. The first two principal component axes (PCA 1 and 2) were significant (p≤0.01) and cumulatively contributed to 73% of the total genotype by environment interaction. In GGE bi-plot analysis using genotypic and environmental scores of the first PCA 1 and lower PCA 2 scores gave high yields (stable genotypes), and genotypes with lower PCA 1 and larger PCA 2 scores had low yields (unstable genotypes), as in the sites tested. Besides, genotypes G3 and G5 were stable across tested locations and gave higher total root yields (43.94t ha-1 and 49.34 t ha-1), respectively). However, G5 was recommended for possible release for wide adaptability in West Hararghe Zone and similar agro-ecology in the country. Res. Agric. Livest. Fish. 10(1): 43-52